2021
DOI: 10.3389/fneur.2021.726437
|View full text |Cite
|
Sign up to set email alerts
|

Facial Paresthesia, a Rare Manifestation of Hereditary Neuropathy With Liability to Pressure Palsies: A Case Report

Abstract: Trigeminal sensory neuropathy can be caused by a variety of conditions, including local, traumatic, iatrogenic, or systemic causes. Diagnosis and management remain a challenge for maxillofacial surgeons and neurologists. Therefore, a good clinical examination and objective tests and imaging are needed when diagnosing patients who present with facial numbness. We present a case with spontaneous episodes of facial paresthesia. He was diagnosed with hereditary neuropathy with liability to pressure palsies (HNPP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…47,48 Cranial neuropathies are rare. 49,50 The symptoms and deficits from the acute attacks typically resolve within a few weeks, but residual deficits can occur. In one study, persistent motor deficits of MRC 3/5 or less at 3 months were observed in 15% of patients.…”
Section: Hereditary Neuropathy With Liability To Pressure Palsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 Cranial neuropathies are rare. 49,50 The symptoms and deficits from the acute attacks typically resolve within a few weeks, but residual deficits can occur. In one study, persistent motor deficits of MRC 3/5 or less at 3 months were observed in 15% of patients.…”
Section: Hereditary Neuropathy With Liability To Pressure Palsiesmentioning
confidence: 99%
“…Brachial plexopathy occurs in approximately one-third of patients and is more common in women 47,48 . Cranial neuropathies are rare 49,50 . The symptoms and deficits from the acute attacks typically resolve within a few weeks, but residual deficits can occur.…”
Section: Hereditary Neuropathy With Liability To Pressure Palsiesmentioning
confidence: 99%